Proceedings of the ACM Symposium on Applied Perception 2013
DOI: 10.1145/2492494.2492500
|View full text |Cite
|
Sign up to set email alerts
|

The effect of posture and dynamics on the perception of emotion

Abstract: AngerDisgust Fear Happiness Sadness Surprise AbstractMotion capture remains a popular and widely-used method for animating virtual characters. However, all practical applications of motion capture rely on motion editing techniques to increase the reusability and flexibility of captured motions. Because humans are proficient in detecting and interpreting subtle details in human motion, understanding the perceptual consequences of motion editing is essential. Thus in this work, we perform three experiments to g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…In computer animation, both body motions and facial expressions are two popular mediums for a character to express the emotion. To understand and represent the emotion, there is an increasing focus on analyzing how motion emotion is perceived by users . While it is possible to identify emotion automatically from motion, synthesizing motion with controllable emotion intensity is much more challenging due to the high dimensionality in the control parameters as well as the complex relationship between such control parameters and the emotional expressions.…”
Section: Introductionmentioning
confidence: 99%
“…In computer animation, both body motions and facial expressions are two popular mediums for a character to express the emotion. To understand and represent the emotion, there is an increasing focus on analyzing how motion emotion is perceived by users . While it is possible to identify emotion automatically from motion, synthesizing motion with controllable emotion intensity is much more challenging due to the high dimensionality in the control parameters as well as the complex relationship between such control parameters and the emotional expressions.…”
Section: Introductionmentioning
confidence: 99%
“…Perception of emotions with static vs. dynamic stimuli was investigated and as expected, it was observed that dynamic stimuli are easier to perceive [78]. In [19] Normoyle et al studied the effects of motion editing on perceived intensities of affects especially with respect to changes in dynamics and posture. Moreover, they concluded that the upper body contains more indicators for perception of affect and that while changes in posture can change the perceived affect, changes in dynamics impacts the perceived intensities.…”
Section: Human Motion: Perceptionmentioning
confidence: 87%
“…Analysis of the features in terms of both execution as well as perception is the first route. For these studies, there have been significant amounts of research carried out by the physiology and psychology [16] communities as well as the multimedia community [19]. These studies can be used indirectly towards computational methods for extraction and modeling means as well as interpreting the outcomes of the other two components of motion studies.…”
Section: List Of Abbreviationsmentioning
confidence: 99%
See 2 more Smart Citations